PROGRAM PENINGKATAN TOLERANSI SOSIAL KEMANUSIAAN UMAT BERAGAMA DALAM KOMUNIKASI VERBAL DI DUSUN LENDANG GUAR TIMUR, LOMBOK BARAT - Ni Luh Sinar Ayu Ratna Dewi; I Kayan Kariyadi; Ni Putu Sudewi Budhawati; I Wayan Sumertha; I Made Agus Yudhiarsana; Made Sutha Yadnya (Universitas Mataram, 2023)
The residents of Lendang Guar hamlet are residents who are very difficult to access from the West Lombok Regency Highway to get to other places, this position is very difficult to reach by local transportation so social understanding is very closed. This is necessary sharpening insights regarding Hinduism actually needs to be recalled so that there are no deviations from the teachings of Hinduism. Going down directly to the hamlet is carried out continuously to produce what is expected by all levels of society to maintain inter- and inter-religious harmony. The results that are felt and obtained by the community with this community service program are changes in life expectancy or life status that are confined to the surrounding area, now an understanding of inter- and inter-religious tolerance has been gained. What is even more special is the belief that the sons and daughters of the regions have the opportunity to pursue education up to tertiary institutions to graduate postgraduate. The implementation of community service has been carried out and received a welcome and understanding of the essence of the teachings of Hinduism with direct verbal communication.